China-Central Asia Cooperation: Old Wine in a New Bottle, or a New Cocktail in the Making? - Tony Tai-Ting Liu (Journal of Central Asian Studies)
In recent years, Central Asia has garnered much attention from the international community, thanks in part to the Belt and Road Initiative and China’s continuing expansion in Eurasia, and the renewed interest of the United States, Japan, India, and the European Union in the region. The latter has spurred an institutional race in the region that bares semblance to the Great Game, a term popularized by Peter Hopkirk to describe competition between Russia and Great Britain in Central Asia in the 19th century. The emerging “New Great Game” is centered on Central Asia plus dialogues that a number of countries have established to gain an inroad into Central Asia and establish cooperation with the five “Stan” countries. Resting on its geopolitical and economic advantages, China has established a series of communication channels with countries in Central Asia, including the most recent establishments of the China-Central Asia Cooperation or the C+C5 in 2020, and the C+C5 Summit in 2023. Together with the Belt and Road Initiative and the Shanghai Cooperation Organization, China has shown clear interest in expanding its influence westward and shaping a favorable regional community in Central Asia. Centered on China-Central Asia Cooperation, this article examines China’s latest endeavor in Central Asia and other similar initiatives in the region that jointly serve as the driving force for the New Great Game. This article suggests that the C+C5 is not merely a branch of existing initiatives, but a new initiative that holds great potential for further cooperation between China and Central Asia.